Paraboea angustifolia (Gesneriaceae): a new species from limestone areas in northern Guangxi, China - Xu, Wei-Bin; Huang, Yu-Song; Wei, Guo-Fu; Tan, Wei-Ning; Liu, Yan (Phytotaxa, 2012)
Paraboea angustifolia is a new species of Gesneriaceae from Guangxi, China, which is here described and illustrated. It is similar to Paraboea dictyoneura in its corolla shape, but P. angustifolia can be distinguished by its linear-oblanceolate leaf blade measuring 8–30 × 1.5–3.0 cm (vs. oblanceolate to narrowly obovate-elliptic, 7–15 × 2.0–4.5 cm), 4–10 times (vs. 2.0–3.5 times) as long as wide, and a peduncle of 3–7 cm (vs. 8–21 cm), normally shorter than the leaves. Its capsules are nearly straight.